Faktor Penilaian Niat Pembelian Berkelanjutan Dalam Konteks Platform Belanja Online Shopee Pada Mahasiswa S1 Manajemen Universitas Dharma Andalas - Intan permata sari; Nofri Yendra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study was conducted on undergraduate students of Management at Dharma Andalas University with the title "Assessment Factors of Continuous Purchase Intention in the Context of the Shopee Online Shopping Platform on Undergraduate Students of Management at Dharma Andalas University." The main objective of this study was to examine the effect of product assessment, price assessment, and convenience assessment on continuous purchase intention in students who use the Shopee platform. The data in this study are presented in the form of frequency distribution, where each respondent provides an assessment according to the conditions they experience. The sampling technique uses purposive sampling, which means that sample selection is based on certain characteristics. The sample criteria in this study are: (1) undergraduate students of Management at Dharma Andalas University, (2) have used online shopping platforms, and (3) have intended to make continuous purchases at Shopee The data sources for this study consist of primary data and secondary data. Primary data were obtained directly from respondents through questionnaires distributed to undergraduate Management students of the 2018–2024 intake. Meanwhile, secondary data were obtained from books, literature, articles, and other sources on the internet. Data collection was carried out through observation and questionnaire techniques. The research instrument in the form of a questionnaire was compiled using a Likert scale, where each variable is described into indicators which are then developed into statements or questions. Respondents provided answers with a gradation scale from very positive to very negative. The characteristics of respondents observed in this study included gender, age, and online shopping experience. In this study, a normality test was conducted to determine whether the residuals were normally distributed, as well as a multicollinearity test to test the relationship between independent variables. The results of the analysis showed that there were no problems with normality, multicollinearity, or heteroscedasticity. The test results show that partially, Product assessment has a positive and significant effect on continuous purchase intention. Price assessment has a positive and significant effect on continuous purchase intention. Convenience assessment has a positive and significant effect on continuous purchase intention. Simultaneously, the three independent variables (product assessment, price assessment, and convenience assessment) have a positive and significant effect on continuous purchase intention. Thus, the hypothesis stating that there is a joint influence between the independent variables on the dependent variable can be accepted